2016
DOI: 10.4103/1735-3327.182184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of threshold response and appropriate electrode placement site for electric pulp testing in fluorosed anterior teeth: An in vivo study

Abstract: Background:Accurate diagnosis is key to success. Diagnosing the pulpal status in varied clinical situations poses a challenge to the clinician. Electric pulp test (EPT) is one of the valuable attempts in evaluating the sensibility of pulp tissue. The aim of this study was to find out and compare the threshold levels and optimal electrode placement site for EPT in fluorosed and nonfluorosed anterior teeth.Materials and Methodology:Eighty volunteers recruited for this study were divided into two groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Other variables to consider are: psychological and behavioral factors (apprehension or Hawthorne effect) and biological factors (hormonal levels and neurological differences). On the other hand, researchers did not report differences between genders [16, 25, 26]. In terms of age, the sites with predictive values ≥0.70 and accuracy ≥0.75 were observed in all the age groups, but the highest values of false positives were identified in the male group from 51 to 65 years (frequency = 15) and the false negatives in the female group from 51 to 65 years (frequency = 4).…”
Section: Discussionmentioning
confidence: 96%
“…Other variables to consider are: psychological and behavioral factors (apprehension or Hawthorne effect) and biological factors (hormonal levels and neurological differences). On the other hand, researchers did not report differences between genders [16, 25, 26]. In terms of age, the sites with predictive values ≥0.70 and accuracy ≥0.75 were observed in all the age groups, but the highest values of false positives were identified in the male group from 51 to 65 years (frequency = 15) and the false negatives in the female group from 51 to 65 years (frequency = 4).…”
Section: Discussionmentioning
confidence: 96%
“…An inappropriate test site may reduce the specificity and sensitivity of the EPT (9), such as a false‐negative response in a tooth that is still vital. Several studies (6,7,9,10–13) have reported varying sites as appropriate and optimal for the least amount of electric current needed to elicit response from electric pulp testing on different teeth. There is, however, no consensus on this.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, no consensus on this. Like several others (6,9,10,21), the current study employed the maxillary central incisors. The choice was based on their location and ease of access, reduced incisal edge wear unlike what can be commonly seen with the posterior teeth and the pulp size reduction that follows secondary dentin deposition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations